An innovative viable model for community-owned solar PV projects without FIT: Comprehensive techno-economic assessment. (November 2020) - Mirzania, Pegah; Balta-Ozkan, Nazmiye; Ford, Andy
Abstract: The progressive withdrawal of the Feed-in-Tariff provided by the UK government has left community-owned solar photovoltaic projects facing significant financial challenges. They urgently need to develop alternative business models that will enable them to develop new projects and recuperate their costs in this post-subsidy era. One promising possibility is the incorporation of storage technology. However, currently it cannot be denied that the financial viability of this type of model is in question. This paper investigates whether and how integrated solar and battery storage system would be financially viable, using the System Advisor Model as a simulation tool to conduct techno-economic analyses. This paper proposes an innovative model designated as, the 'Community-owned Energy Storage' model. This model proposes that community-owned solar projects should sell their locally generated electricity under a Time of Use Power Purchase Agreement (TOU PPA). Results demonstrated under the developed model of community-owned solar projects can fully restore the economic viability and become financially attractive if they could utilise a combination of TOU PPA and demand-side response (DSR) services. This paper, therefore, recommends that the UK government should promote and facilitate the TOU PPA and encourage suppliers to involve local energy projects within the provision of DSR. Highlights: Alternative models needed to recuperate income of CRE 1 projects in the post-subsidy. This paper proposes a novel model designated as, the 'Community-owned Energy Storage' model. CRE projects become financially attractive if they utilise a combination of different revenues. CRE projects should be enabled to sell their electricity directly to local customers. The suppliers should be encouraged to involve CRE projects in the provision of DSR 2